MODULAR SMART ELECTRONIC SWINGHANDLE WITH REMOTE CONTROL BASED INTERNET OF THINGS (IOT) - Keklik, Emre; Gunes, Engin; Yasar, Mahir; Aydin, S. Mert; Akdogan, Anil (TECHNICAL UNIV CLUJ-NAPOCA, FAC MACHINE BUILDING DEPT SYSTEMS ENG, 2022)
The traditional mechanical locks used in the industry are starting to leave their place to electronic lock models in which user input and output information can be monitored, remote authorization can be provided and lock status can be monitored with the developing technology. Due to the priority of security in lock systems, the need for electronic locks, which are safer than mechanical locks, has increased even more. The electronic swinghandles are especially preferred in usage areas such as data centers, server rooms and telecommunication cabinets. In this study, it is aimed to remotely control electronic swinghandle locks and monitor their open/closed states thanks to the Internet of Things (IoT) based smart control system via mobile application and/or web application.
Keywords: Electronic Swinghandle Lock; Industrial Lock; Internet of Things; IoT; NodeMCU; Smart Lock; Mechanics